Device discovery and configuration scheme for Internet of things - Ashraf, Qazi Mamoon; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Khan, Sheroz (Institute of Electrical and Electronics Engineers, Inc., 2016)
The term “Internet of Things” (IIoT) refers to the expansion of Internet technologies to include smart objects by extensive deployment of exclusively identifiable distributed communication devices. The management of configuration in these devices, in particular, is a challenge due to the high heterogeneity in different communication protocols, communication sequences, and processing capabilities. We propose a device configuration management scheme for IoT inspired by IBM’s autonomic control loop. This scheme is capable of discovering sensors despite their heterogeneity in their offered services. Furthermore, by enabling configuration management, dependence of IoT systems on user interfence be minimized. Index Terms— Internet of Things, Management, Wireless Sensor Networks, Contiki, Autonimy, self-configuration, Machine to Machine.